PERANCANGAN RC (REMOTE CONTROL) BOAT PATROL 80 CM DENGAN PROPULSI WATERJET - Wiwin Sulistyawati; Purwo Joko Suranto (Bina Teknika, 2016)
The government is still struggling to secure all the waters of the archipelago in maintaining and overseeing the security of its territory. This is due to the many islands that need human resources (HR) and require a lot of high-tech ships. So it is necessary to design a robot ElectricRemote Control Waterjet Patrol 80 (ERC_WP 80) which could serve as patrol boats and destroyers. Waterjet propulsion drive system has a motion if the vessel was excellent at relatively high speed boats and has good acceleration capabilities. Boats with jet propulsion system can operate in very shallow waters. This is due to all parts of the engine located under the hull, including propeller, shaft and shaft house. Waterjet advantages compared with the steering system / rudder is conventional waterjet propulsion system is able to turn the steering wheel with a smaller angle. Maneuverability and good seakeeping of a ship is strongly influenced by the shape of the hull. Selection of the hull shape is designed to perform parametric studies hull of the vessel Fast Patrol Boats comparator (KPC) 14 1 228 m and the vessel JS Patrol. On the back of the boat is made with a slope angle (chine angle) of about 20 degrees in order to gain the necessary lifting force without reducing the stability of the ship. While at the front end of the ship made a slope angle of about 30 degrees with the intent facilitate ship moving at high speed and reduce the impact when the waves break. Unmanned patrol boats are designed using radio control GensAce 4S 3300mAh